Effect of acupoint application of Traditional Chinese Medicine on recovery of gastrointestinal function after cesarean section (中药穴位敷贴促进剖宫产术后胃肠功能恢复的效果观察) - PENG Rufeng (彭茹凤); LI Fengmin (黎凤民); HUANG Ling (黄翎); HUANG Huan (黄环); SU Qiumei (苏秋梅) (中西医结合护理)
Objective To investigate the effect of acupoint application of Traditional Chinese Medicine (TCM)on recovery of gastrointestinal function after cesarean section. Methods Totally 200 puerperae undergoing cesarean section were randomly divided into observation group and control group, with 100 cases in each group. All puerperae received routine postpartum care, and those in the observation group were given TCM acupoint application. The bowel sound recovery time, time of anal exhaust and first time of defecation were recorded, and abdominal distension was measured at 24 h and 48 h after cesarean section. Results The bowel sound recovery time, time of anal exhaust and first time of defecation were shorter in the observation group than those in the control group(P＜0. 05). The incidence of abdominal distension in the observation group was lower than that in the control group at 24 h and 48 h after cesarean section respectively (P＜0. 05). Conclusion TCM acupoint application on Shenque (CV 8), bilateral Yongquan (KI 1), bilateral Shenshu(BL 23) is effective on recovery of puerperae’s gastrointestinal function, reduce the risk of abdominal distension and improve postpartum quality of life. (目的 观察自制中药穴位敷贴促进剖宫产术后胃肠功能恢复的效果。方法 200例行剖宫产术的产妇随机分为观察组和对照组, 各100例。对照组给予剖宫产后常规护理, 观察组在对照组基础上给予自制中药敷贴穴位干预。观察记录2组产妇术后肠鸣音恢复时间、首次肛门排气时间、首次肛门排便时间, 记录术后24 h、48 h腹胀情况。结果 观察组术后肠鸣音恢复时间、首次肛门排气时间、首次排便时间均早于对照组, 差异有统计学意义(P＜0. 05)。观察组术后24 h和48 h腹胀发生率均低于对照组相应时间, 差异有统计学意义(P＜0. 05)。结论 运用自制中药敷贴神阙穴、双涌泉穴、双肾俞穴, 有助于剖宫产术后胃肠功能恢复, 减少腹胀的发生, 提高产妇产后生活质量。)